2018
DOI: 10.1039/c7sm02424j
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide “revisited”: UCST-type reversible thermoresponsive properties in aqueous alcoholic solutions

Abstract: Combining experiments and all-atom molecular dynamics simulations, we study the conformational behavior of polyacrylamide (PAM) in aqueous alcohol mixtures over a wide range of temperatures. This study shows that even when the microscopic interaction is dictated by hydrogen bonding, unlike its counterparts that present a lower critical solution temperature (LCST), PAM shows a counterintuitive tunable upper critical solution temperature (UCST)-type phase transition in water/alcohol mixtures that was not reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…AAm on the other hand is an example for a non-TSP in watery solution. 39 NMAAm has been conjectured to exhibit an LCST above 373 K, in aqueous solution. 4 , 22 To our knowledge, this assertion has hitherto not been confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…AAm on the other hand is an example for a non-TSP in watery solution. 39 NMAAm has been conjectured to exhibit an LCST above 373 K, in aqueous solution. 4 , 22 To our knowledge, this assertion has hitherto not been confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to LCST-type VPTT, studies on the polymers with UCST or UCST-type VPTT have been reported at a much lessened extent [ 38 ]. Polysulfobetaine [ 39 ] and poly( N -acrylolyglyciamide) [ 40 42 ] are the polymers reportedly with UCST in water, while polyacryamide [ 43 ] and poly(acetoacetoxyethyl methacrylate) [ 44 ] are reported to exhibit UCST in binary ethanol/water solvent mixture. Roth et al demonstrated that poly[oligo(ethylene glycol) methyl ether methacrylate], (POEGMA), exhibited UCST in a large variety of aliphatic alcohols and that the UCST phase transition temperature was dependent on the structure, molecular weight, and the concentration of POEGMA, as well as the solvent, co-solvents [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, hydrogel particles with their R h around 10 nm, determined by DLS, were often reported. Diverse examples are available, such as polyacrylamide above its UCST in aqueous alcohol solutions [ 43 ] and 4-propoxyazobenzene-terminated PNIPAM in aqueous solution below its LCST [ 47 ]. And R h as small as 2 to 3 nm was reported for an OEG-based responsive polymer below its LCST [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses of poly[ N‐ (6‐acetamidopyridin‐2‐yl)acrylamide] PNAcAPAM and polyacrylamide (PAM) were performed according to previous works.…”
Section: Methodsmentioning
confidence: 99%